2017
DOI: 10.1001/jama.2017.0693
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Treatment and Subsequent Neoplasm Risk Among 5-Year Survivors of Childhood Cancer, 1970-2015

Abstract: IMPORTANCE Cancer treatments are associated with subsequent neoplasms in survivors of childhood cancer. It is unknown whether temporal changes in therapy are associated with changes in subsequent neoplasm risk.OBJECTIVE To quantify the association between temporal changes in treatment dosing and subsequent neoplasm risk.DESIGN, SETTING, AND PARTICIPANTS Retrospective, multicenter cohort study of 5-year cancer survivors diagnosed before age 21 years from pediatric tertiary hospitals in the United States and Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
196
5
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(219 citation statements)
references
References 35 publications
8
196
5
5
Order By: Relevance
“…1). Thyroid cancer, specifically papillary thyroid carcinoma (PTC), is one of the most frequently diagnosed subsequent primary malignancies in childhood cancer survivors [28, 85, 86]. Survivors of childhood Hodgkin disease, for example, are 18.3-fold more likely to develop PTC [26], although benign thyroid nodules are still more common [31].…”
Section: Radiation-induced Thyroid Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…1). Thyroid cancer, specifically papillary thyroid carcinoma (PTC), is one of the most frequently diagnosed subsequent primary malignancies in childhood cancer survivors [28, 85, 86]. Survivors of childhood Hodgkin disease, for example, are 18.3-fold more likely to develop PTC [26], although benign thyroid nodules are still more common [31].…”
Section: Radiation-induced Thyroid Diseasementioning
confidence: 99%
“…Typically, the latency period is long, and studies from the CCSS and the British CCSS cohorts showed a median time to occurrence around 19–20 years after treatment of the first primary cancer [32, 85]. In some studies, the reported shorter latency periods could be in part attributed to the incorporation of routine ultrasound screening in at-risk cancer survivors [86, 89].…”
Section: Radiation-induced Thyroid Diseasementioning
confidence: 99%
“…Currently, since most children have entered late‐stage retinoblastoma that represented high chance of ocular extraction, early diagnosis and treatment for retinoblastoma appeared to be quite critical 2, 3. To save children's visual function,4 diverse treatment strategies have been developed for varying degrees of retinoblastoma 5.…”
Section: Introductionmentioning
confidence: 99%
“…2 However, curative therapy for childhood malignancies places many survivors at increased risk for late effects of treatment, including second primary malignancies (SPMs). [4][5][6][7][8][9] Although fewer than 3% of childhood cancer survivors develop an SPM within 15 years of their initial diagnosis, 4 the cumulative incidence approaches 10% by 30 years after the diagnosis in high-risk populations. 3 In particular, patients treated with radiotherapy, anthracyclines, platinum agents, or alkylating agents are vulnerable to subsequent neoplasms.…”
Section: Introductionmentioning
confidence: 99%